Finnish national identity in the picture book Tatun ja Patun Suomi [Tatu and Patu's Finland] and its relation to the country's multicultural integration - Watanabe , Tomoko (2009)
The world is shrinking, and people cross the borders for various reasons such as better education, work and other opportunities in this century. Multiculturalism and multicultural integration are the issues that many nations are struggling with. To integrate people with various backgrounds (ethnical difference, culture, religion and so forth) is not easy, but it is an important issue to work towards. Finland started to take large numbers of immigrants since 1980’s in order to solve the problem of labor shortage in society. Because of this and globalization, the national identity as being a Finn and also what is Finnish have been influenced. At the same time, Finnish people’s attitude towards immigrants and/or other ethnical minority groups reveals that they are not a part of society. In order to develop the awareness of multicultural integration and to achieve a better integration, various sectors in the society had been making efforts. As if it was an addition to those programs held by the central government or local organizations, the book Tatun ja Patun Suomi [Tatu and Patu’s Finland] by Aino Havukainen and Sami Toivonen was published in 2007 when Finland was celebrating the 90th anniversary of its independence. The idea of the picture book may be to pass the idea of positive integration as well as positive national identity to the residents of Finland, which then might influence their actions in the future. The thesis shows that the picture book can be an unofficial education tool for multicultural integration in the society. This thesis covers various aspects (visual and textual study, identity issues, color studies, translation studies and media study which the picture book has as part of the media to reach the people. fi=Opinnäytetyö kokotekstinä PDF-muodossa.|en=Thesis fulltext in PDF format.|sv=Lärdomsprov tillgängligt som fulltext i PDF-format|